A Literature Survey on Biological Activities of Thiazolidine Derivatives - Vijaiyalakshmi R; Anbazhagan S; Subasri B; Divya J; Madeshwaran G; Eniyan M; Surya Prakash k (International Journal of Cheminformatics, 2025)
Hetercyclic compounds play a vital role in both chemical and life sciences. Among them ,thiazolidinone represent a significant class, characterized by a five- membered saturated ring containing both sulfur and nitrogen atoms. Structurally, thiazolidinones are derived from thiazole, with sulfur position at the 1-position, nitrogen at the 3-position , and a carbonyl group typically located at the 2-, 4-, or 5- position are possible, though structural and functional diversity is most stronghly influenced by the group attached at the 2-position carbon 4- Thiazolidinones , in particular , are derivatives of thiazolidine featuring a carbonyl group in thiazolidinones is generally unreactive , its interaction with Lawessons reagent can yeild corresponding 4-thione derivatives . The presence of hetero atom such as nitrogen , sulfur, and oxygen contribute to the broad biological activity many heterocyclic compounds.
Keywords: Antimicrobial drug; Biological activities; Tuberculosis; hetercyclic compounds; thiazolidine